Recurrence and revision rates with arthroscopic bankart repair compared with the Latarjet Procedure in competitive rugby players with glenohumeral instability and a glenoid bone loss < 20% - Rossi, L. A.; Tanoira, I.; Gorodischer, T.; Pasqualini, I.; Ranalletta, M. (The American Journal of Sports Medicine, 2021)
Background: There is a lack of evidence in the literature comparing outcomes between the arthroscopic Bankart repair and the Latarjet procedure in competitive rugby players with glenohumeral instability and a glenoid bone loss <20%.